Prevalence of haemoparasitic infections in dairy cattle (Friesian breeds) at nagari integrated dairy farms, Gauta-Nike village, Keffi local government area, Nasarawa state, north central of Nigeria - M. Abdullahi, S.; Idris, Y.; A. Alhaji, M.; Kabir, I.; M. Abubakar, S. (Scientific Journal of Zoology, 2014)
The of prevalence ofhaemoparasites of cattle located in Nagari Integrated Farms, Gauta-NikeVillage, Keffi Local Government Area, Nasarawa State, Nigeria was conducted inOctober 2012 where 50 Friesian cattle (male and females) are kept on intensivesystem of management were randomly selected. Blood samples were collected in ananticoagulant sample bottle and submitted to the Parasitology Laboratory ofFaculty of Veterinary Medicine, Ahmadu Bello University Zaria, Kaduna state ofNigeria for parasitological examination. Giemsa stained thin blood smears wereexamined for hemoparasites and Hematocrit Centrifuge Technique (HCT) was usedto determine the presence of motile parasites. An overall prevalence of 90%(82% female and 8% male) was recorded for all samples examined, 21 (42%) wereinfected with Anaplasma marginale, Theileria mutans shows 20 (40%) prevalenceand 4 (8%) were infected by Babesia bigemina. Mixed infection between Anaplasmamarginale and Babesia bigemina revealed 2 (4%) while Anaplasma marginale andTheileria mutans was 7 (14%). There was a significant difference (P > 0.05)in infections caused by Anaplasma marginale, Babesia bigemina and Theileriamutans (Table 1) and also between sexes(Table 3), but there was no significant difference (P<0.05) between any of the mixedinfections observed (Table 2). The result of this study shows thesehemoparasites are endemic in the cattle under study which may result in seriousdisease conditions when such animals are subjected to stressful condition.